The influence of supervision by the head of medical services and nurse performance on patient safety at Aek Kanopan Regional General Hospital - Siregar, Fitria Desiana; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Patient safety is a primary priority in healthcare services; however, adverse events persist and are often associated with nurse performance and weak supervision. This study aimed to analyze the influence of supervision by the Head of Medical Services and the performance of inpatient ward nurses on patient safety at Aek Kanopan Regional General Hospital, North Labuhanbatu Regency. Methods: This quantitative study employed a cross-sectional design. The study population comprised all 120 implementing nurses in the inpatient wards, who were also recruited as the total sample. Data were collected using a structured questionnaire measuring nurse perceptions of supervision, performance, and patient safety implementation. Data analysis included univariate and bivariate analyses using the Chi-Square test. Results: The majority of respondents rated supervision as good (84.2%), nurse performance as good (84.2%), and patient safety as good (84.2%). Bivariate analysis demonstrated a significant association between supervision and patient safety (p=0.000) and between nurse performance and patient safety (p=0.000). Conclusion: This study concludes that effective supervision by department heads and optimal nurse performance contribute significantly to improved patient safety. Hospital management is advised to strengthen supervisory capacity and invest in continuing professional development programs for nurses.